Versions of Pragmatic Liberalism: from Rorty back to Dewey - Dubniak, Zlatyslav (Journal of Education Culture and Society, 2021)
Aim. The aim of this study is to analyze and evaluate two versions of the theory of liberalism which emerged within the philosophical tradition of pragmatism: Richard Rorty’s “ironic liberalism” and John Dewey’s “renascent liberalism”. Methods. The study is based on: 1) comparative analysis, which shows the differences and points of contact between Dewey’s classical pragmatism and Rorty’s neo-pragmatism, in particular, between different versions of their liberal theories; 2) critical analysis, which made it possible to identify the shortcomings and advantages in the arguments of the above-mentioned philosophers. Results. The author analyzed Rorty’s and Dewey’s theories of liberalism in relation to their theories of reality, human specificity, and ethics. In this way, the specific liberal views of these American philosophers on such issues as the relationship between private and public, the main goals of politics, and the values of the social order were explicated. It allowed offering a thorough critique of Rorty’s “ironic liberalism”, and supporting of Dewey’s “renascent liberalism”. Conclusion. While Dewey saw the mission of liberalism in enabling individuals to improve their experience, Rorty insisted on the need for a liberal policy of providing the basic conditions for individual self-creation. The main disadvantage of Rorty’s neo-pragmatism, and, in particular, “ironic liberalism”, was the exclusion from the philosophy of the modifying tools of human behavior, which were expressed by the concepts of “good” or “virtue”, in Dewey’s “renascent liberalism”. This circumstance necessitates a return from Rorty back to Dewey in the discussions on pragmatic liberalism. Key words: philosophy of pragmatism, Richard Rorty, John Dewey, historicism, naturalism, liberalism.